Sustainable tourism competitiveness analysis for regional economic enhancement in West Java - Muhammad Wahyu Hamijaya; Restu Akbar Suryaman (Universitas Merdeka Malang, 2023)
Tourism is an economic sector that has a large multiplier effect on other economic activities, so that for certain areas that have tourism economic potential, it is very important to pay attention to and increase the competitiveness of tourism as a source of regional economic growth. This research aims to analyze the competitiveness of tourism in districts/cities in West Java. This research uses explanatory analysis and competitiveness mapping methods to identify superior tourism indicators in districts/cities in West Java. The indicators used in this research include the tourism impact index, human resources index, social development index, price competitiveness index and openness indicator. The results of the analysis found that there are only 4 regions that have superior tourism competitiveness in all indicators, namely Cirebon Regency, Indramayu Regency, Sukabumi City and Bekasi City. Based on the results of the analysis, this research recommends that the West Java Government and Regency/City Governments, apart from maintaining the attractiveness of tourism, also need to pay attention to competitiveness aspects so that it is hoped that tourism development in West Java can pay attention to sustainability aspects